Kahoot Application in English Language Teaching (ELT) Context: An Alternative Learning Strategy - Putri, Nunung Susilo (Elsya : Journal of English Language Studies, 2019)
This research was designed in descriptive qualitative research. Data were collected from several related works of literature on the application of Kahoot online application in English classrooms. This present study has taken pointers from previous studies that have proven the effectiveness of using video as a learning medium for students, especially in EFL classes. Also, it not only gives students pleasure to learn but also can make students more active and comfortable in the learning process. Besides, the teacher, as a model, must also know how to deliver excellent material using Kahoot online application. Moreover, before using this online application as a medium for teaching, teachers must have a step by step plan of what the teacher must do during teaching and learning. This result has been proven around the globe by many scholars that teaching English using media such as Kahoot is one effective strategy that makes students enjoy the teaching and learning process.